ANALISIS IMPELEMNTASI KEADILAN RESTORATIF DI KEJAKSAAN NEGERI BOALEMO - Muhammad Syarif Pomanto (Universitas Harapan Medan, 2026)
This study aims to analyze the implementation of restorative justice at the Boalemo District Prosecutor’s Office and to identify factors affecting its effectiveness. The research employs an empirical legal approach, using data collected through interviews, observations, and document analysis, which are then examined qualitatively. The findings indicate that, normatively, restorative justice has a strong legal foundation and has been implemented in accordance with Prosecutor Regulation No. 15 of 2020. However, empirically, its implementation remains suboptimal, as reflected in the relatively low number of cases resolved through this approach despite an increase in criminal cases. The practice of restorative justice in Boalemo can be categorized as semi-restorative, where it adopts fundamental principles but remains largely administrative and has not fully achieved comprehensive recovery. Several multidimensional obstacles are identified, including ambiguous legal substance, limited capacity of law enforcement officers, inadequate facilities, low public awareness, and dualism in legal culture. Therefore, efforts such as improving prosecutors’ capacity, standardizing mediation procedures, enhancing infrastructure, and increasing public awareness are necessary to achieve a more effective, humane, and sustainable restorative justice system.